2018
DOI: 10.3390/su10051591
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership, Performance, and Sustainability of Micro-Enterprises in Malaysia

Abstract: This study probed into the impact of entrepreneurial leadership dimensions (i.e., responsibility, accountability, analytical thinking, and emotional intelligence) on the performance and sustainability of micro-enterprises in Kelantan, Malaysia, through the lens of resource-based view (RBV) theory. Through the implementation of a cross-sectional design, data were randomly gathered from 403 micro-entrepreneurs whose names appeared in the list of low-income households registered under "Majlis Amanah Rakyat" Kelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 78 publications
3
82
0
2
Order By: Relevance
“…The quality of work life positively and significantly influences employee job satisfaction, and employee loyalty [20]. Additionally, Al Mamun et al [21], Cantele, and Zardini [22], Delmas, and Pekovic [23], Pintão et al [24], and Dongho [25] referred to employee satisfaction as one of many challenges, since the productivity of employees was crucial to the company's success or failure.…”
Section: Sustainable Human Resource Management Literaturementioning
confidence: 99%
“…The quality of work life positively and significantly influences employee job satisfaction, and employee loyalty [20]. Additionally, Al Mamun et al [21], Cantele, and Zardini [22], Delmas, and Pekovic [23], Pintão et al [24], and Dongho [25] referred to employee satisfaction as one of many challenges, since the productivity of employees was crucial to the company's success or failure.…”
Section: Sustainable Human Resource Management Literaturementioning
confidence: 99%
“…The Successful Start-up Business Model identifies four factors influencing entrepreneurial success: (1) personality traits, (2) psychological capital, (3) education, skills and knowledge representing the human capital, and (4) networks and connections representing the social capital of entrepreneurs [60]. Other scholars found that responsibility, accountability, and emotional intelligence have positive impact on micro-enterprise performances [61] and that positive outlook on life, business success and business demand predict the business success [62]. Personal characteristics of entrepreneurs such as self-confidence, task-result orientation, in-depth planning of the business future and the use of a unique business model support the enterprises performances [63].…”
Section: Factors Shaping Entrepreneurial Resiliencementioning
confidence: 99%
“…The objective to succeed, ensure sustainability, remain competitive, and to increase business efficiency can only be ensured by satisfying the needs of employees by providing them with good working conditions [17,18]. Additionally, Al Mamun et al [19], Cantele, and Zardini [20], Delmas, and Pekovic [21], Pintão et al [22], and Dongho [23] referred to employee satisfaction as one of many challenges, since the productivity of employees was crucial to the company's success or failure.…”
Section: Introductionmentioning
confidence: 99%